2018
DOI: 10.1002/jcp.27477
|View full text |Cite
|
Sign up to set email alerts
|

Albumin induces CD44 expression in glomerular parietal epithelial cells by activating extracellular signal‐regulated kinase 1/2 pathway

Abstract: De novo expression of CD44 in glomerular parietal epithelial cells (PECs) leads to a prosclerotic and migratory PEC phenotype in glomerulosclerosis. However, the regulatory mechanisms underlying CD44 expression by activated PECs remain largely unknown. This study was performed to examine the mediators responsible for CD44 induction in glomerular PECs in association with diabetes. CD44 expression and localization were evaluated in the glomeruli of Zucker diabetic rat kidneys and primary cultured PECs upon album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Moreover, activation of the ERK1/2 signaling pathway is also required for palmitate-induced OPN and CD44 in renal tubular epithelial cells. These results are in agreement with previous reports showing that ERK1/2 regulates mouse KIM expression physiologically and following ischemic and septic renal injury [26] and that activated ERK1/2 increases CD44 in glomerular parietal epithelial cells [34,35]. Although our in vitro findings support that palmitate may induce the production of inflammatory mediators through the ERK signaling pathway, further in vivo studies are required to examine the signaling pathways involved in lipid overload-related tubular cell injury and inflammatory gene expression in proteinuric kidney disease.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, activation of the ERK1/2 signaling pathway is also required for palmitate-induced OPN and CD44 in renal tubular epithelial cells. These results are in agreement with previous reports showing that ERK1/2 regulates mouse KIM expression physiologically and following ischemic and septic renal injury [26] and that activated ERK1/2 increases CD44 in glomerular parietal epithelial cells [34,35]. Although our in vitro findings support that palmitate may induce the production of inflammatory mediators through the ERK signaling pathway, further in vivo studies are required to examine the signaling pathways involved in lipid overload-related tubular cell injury and inflammatory gene expression in proteinuric kidney disease.…”
Section: Discussionsupporting
confidence: 93%
“…ClC-5, megalin and cubilin positivity was identified in human PECs too (Gianesello et al 2018), expanding the spectrum of possible causes of glomerulosclerosis in patients with Dent disease. It was also shown that rat and murine PECs could internalize albumin under normal and overload conditions, in vivo and in vitro (Zhao et al 2019), suggesting a role for ClC-5 in albumin uptake in these cells as well.…”
Section: Glomerular Damage In Dent Diseasementioning
confidence: 97%
“…Our previous quantitative proteomics study [ 23 ] showed that the ERK1 and ERK2 cascades were the top two biological processes after ICH and that the albumin and ERK1/2 signaling pathways were the top protein-protein interaction networks. Recently, some studies showed that there was an important link between albumin and the mitogen-activated protein kinase (MAPK) extracellular signal-regulated kinase, ERK1/ERK2 in kidney disease, and ERK1/2 signaling pathway was the downstream signal activated by albumin therapy [ 24 , 51 ]. Reich et al found that albumin-activated ERK via EGF receptor in human renal epithelial cells and the generation of ROS after albumin exposure was an important proximate event in the albumin-induced cell signaling [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular signal-regulated kinase (ERK) 1/2, a prototypic subfamily of MAPKs, is considered the top biological factor that participates in oxidative and ER stress [23]. Albumin therapy activates the downstream protein ERK1/2 signaling [24,25]. Previous studies showed that nuclear factor erythroid-related factor 2 (Nrf2) is activated by phosphorylate-ERK1/2 (p-ERK1/2) [26], and Nrf2 then enters the nucleus to promote the transcription of the antioxidantresponsive element-regulated gene heme oxygenase-1 (HO-1), which plays a protective role in cellular defense against OS after ICH [27][28][29].…”
Section: Introductionmentioning
confidence: 99%